An RNA-Based Fluorescent Biosensor for High-Throughput Analysis of the cGAS-cGAMP-STING Pathway. Issue 12 (22nd December 2016) - Bose, Debojit; Su, Yichi; Marcus, Assaf; Raulet, David H.; Hammond, Ming C.
Summary: In mammalian cells, the second messenger (2′–5′, 3′–5′) cyclic guanosine monophosphate-adenosine monophosphate (2′, 3′-cGAMP), is produced by the cytosolic DNA sensor cGAMP synthase (cGAS), and subsequently bound by the stimulator of interferon genes (STING) to trigger interferon response. Thus, the cGAS-cGAMP-STING pathway plays a critical role in pathogen detection, as well as pathophysiological conditions including cancer and autoimmune disorders. However, studying and targeting this immune signaling pathway has been challenging due to the absence of tools for high-throughput analysis. We have engineered an RNA-based fluorescent biosensor that responds to 2′, 3′-cGAMP. The resulting "mix-and-go" cGAS activity assay shows excellent statistical reliability as a high-throughput screening (HTS) assay and distinguishes between direct and indirect cGAS inhibitors. Furthermore, the biosensor enables quantitation of 2′, 3′-cGAMP in mammalian cell lysates. We envision this biosensor-based assay as a resource to study the cGAS-cGAMP-STING pathway in the context of infectious diseases, cancer immunotherapy, and autoimmune diseases. Graphical Abstract: Highlights: A fluorescent biosensor that responds to 2′, 3′-cGAMP was designed A biosensor-based fluorescence turn-on assay detects cGAS activity and inhibition High-throughput analysis via fluorescence plate reader is enabled 2′, 3′-cGAMP levels were quantified in DNA-stimulated L929 cells Abstract : Bose et al. developed a fluorescent biosensor for the mammalian immune signal 2′, 3′-cGAMP that enables high-throughput screening assays and quantitation of cGAS enzyme activity. Biosensor-based assays revealed that DNA intercalators indirectly modulate cGAS activity and quantitated the amount of 2′, 3′-cGAMP produced in DNA-stimulated L929 cells.